Patient's perspectives of living with a precancerous condition: Monoclonal gammopathy of undetermined significance (MGUS). (April 2021) - Murphy, Blain; McShane, Charlene M.; Santin, Olinda; Treanor, Charlene; Byrne, Bronagh; Donnelly, Michael; Anderson, Lesley A.
Abstract: Purpose: The aim of this study was to investigate patient experiences of living with monoclonal gammopathy of undetermined significance (MGUS). Living with a premalignant condition such as MGUS may elicit negative psychosocial effects including increased anxiety and fear of progression to cancer. To date, no study utilising qualitative methodology has explored the lived experiences of MGUS patients. Methods: Data was collected via two focus groups and six telephone interviews. MGUS patients (n=14) were recruited via nurse-led haematology telephone-clinics in Northern Ireland. Interviews were transcribed verbatim and the data subjected to thematic analysis. Outcome: Thematic analysis identified 3 overarching themes; (1) The psychosocial impact of an MGUS diagnosis, (2) Knowledge of MGUS and (3) Experiences of MGUS health services. Patients with MGUS reported experiencing poor psychological adjustment to their condition particularly at the point of diagnosis and approaching follow-up appointments. Feelings of isolation, poor information-provision, increased uncertainty and limited psychosocial support for MGUS patients were also reported. Patients did however reflect positively on their experience of being followed up via nurse-led telephone clinics. Conclusions: Provision of patient friendly information guides at diagnosis, and additional psychosocial support services such as nurse-led telephone clinics and coordinated patient groups may help MGUS patients adjust better to their diagnosis and in doing so improve quality of life in this patient population. Highlights: Patient-friendly information and support is necessary at the point of diagnosis and thereafter. The use of telephone clinics conducted by clinical nurse specialists reduced patient burden and were positively endorsed. Improved HCP communication and diagnosis/follow-up in a non-cancer setting may help the psychosocial wellbeing of patients.